Integrating single-cell RNA sequencing with multi-omics to decode disease microenvironments - Arti Devi; Vaibhav Pathak; Vagish Dwibedi; Jasdeep Singh; Ashish Kumar Pathak; Nancy George; Ashwani Kumar; Gursharan Kaur; Santosh Kumar Rath; Amit Chatterjee (Molecular Biology Reports, 2026)

Multisensor satellite and ground gravity data for delineating near surface signatures for hydrocarbon exploration - A study in the Jaisalmer basin, Rajasthan - Arindam Guha; Ashish Misra; Nikhil Kumar Baranval; Swati Singh; Santosh Garain; S.K. Srivastav; Suparn Pathak; Prakash Chauhan (Remote Sensing Applications: Society and Environment, 2025)

Alzheimer’s disease: from early pathogenesis to novel therapeutic approaches - Santosh Kumar Prajapati; Arjit Pathak; Puneet K. Samaiya (Metabolic Brain Disease, 2024)

Spatial and temporal trend analysis of rainfall in Nagaland (India) using machine learning techniques - Santosh Pathak; Mhalevonuo Chielie; Y Satish; B C Kusre (Journal of Earth System Science, 2024)

Space based Earth observation approach for exploring hydrocarbon prospects in an intracratonic rift basin – A study in north Cambay basin, Gujarat - Arindam Guha; Nikhil Kumar Baranval; Ashish Misra; Swati Singh; M. Shivashankar; Santosh Garain; Subhobroto Mazumder; S. Pathak; K. Vinod Kumar (Advances in Space Research, 2023)

Irrigation water demand and elasticities: a case study of the High Plains aquifer - Santosh Pathak; Naveen C. Adusumilli; Hua Wang; Lal K. Almas (Irrigation Science, 2022)
The agriculture of the Texas High Plains (THP) region is primarily dependent on groundwater irrigation. Changing weather patterns along with competing demands for water resources and other anthropogenic effects have dramatically increased withdrawals from the Ogallala aquifer. In addition to on-farm changes, policy tools based on off-farm mechanisms are equally indispensable in addressing sustainable groundwater use in the THP. One such policy tool is water pricing using estimates of price elasticity of irrigation water demand. This paper estimates the elasticity of irrigation water demand in the THP and assesses the influence of water price on major inputs used in dominant irrigated crops such as corn and cotton. Using the translog profit function on an annual county-level dataset of THP crop production, spanning 23 years (1998–2020), we find that irrigation water demand is price elastic for cotton ( η = – 1.58) but inelastic for corn ( η = – 0.81). Our findings suggest that a non-uniform pricing policy could be a useful tool to promote the efficient use of groundwater for irrigation.

Phosphodiesterase 5 inhibitor sildenafil potentiates the antitumor activity of cisplatin by ROS-mediated apoptosis: a role of deregulated glucose metabolism - Shiv Govind Rawat; Rajan Kumar Tiwari; Pradip Kumar Jaiswara; Vishal Kumar Gupta; Pratishtha Sonker; Naveen Kumar Vishvakarma; Santosh Kumar; Chandramani Pathak; Vibhav Gautam; Ajay Kumar (Apoptosis, 2022)

Risk Aversion and Timber Harvest Strategies: A Case Study of Nonindustrial Private Forest Management in Louisiana - Hua Wang; Naveen Adusumilli; Michael Blazier; Santosh Pathak (Small-scale Forestry, 2022)
Forest owners face many challenges regarding forest management due to the long period from planting to harvest. Along with the economic and environmental factors that influence management actions, the owners' attitude to risk plays a crucial role in forest management decisions. This study shows that understanding the effects of the owner's risk preference for management actions is an important step to form an effective forest policy. The objectives of the study are to (1) assess the economic advantage of forest management alternatives over a range of risk aversion coefficients and (2) determine the financial incentive (risk premium) corresponding to a forest owners' risk attitude. We implemented the stochastic efficiency with respect to a function framework to evaluate a set of fertilization, herbicide, and thinning management alternatives at mid-rotation loblolly pine plantations in Louisiana. Results from this study indicate that forest owner's risk preference affects their decision to select management actions. Financial incentives are substantially different for specific management alternatives between risk-neutral and risk-averse forest owners. The results can guide forest policy development where agencies can modify financial assistance programs to improve the adoption of management actions.

Fish community diversity assessment of protected Saraiyaman wetland in the Ganga River basin, India - Kripal Datt Joshi; Ajey Kumar Pathak; Santosh Kumar; Rajesh Dayal; Ajay Kumar Singh; Ravi Kumar; G. Kantharajan; Vindhya Mohindra; Kuldeep K. Lal (Community Ecology, 2022)

Impact of the Federal Conservation Program Participation on Conservation Practice Adoption Intensity in Louisiana, USA - Santosh Pathak; Krishna P. Paudel; Naveen C. Adusumilli (Environmental Management, 2021)

Flood vulnerability and its influencing factors - Santosh Pathak; Hari Krishna Panta; Thaneshwar Bhandari; Krishna P. Paudel (Natural Hazards, 2020)

Distribution of vehicular pollutants in street canyons of Varanasi, India: a different case - Santosh K. Prajapati; B. D. Tripathi; Vinita Pathak (Environmental Monitoring and Assessment, 2009)

Analysis of a village chicken production system and performance of improved dual purpose chickens under a subtropical hill agro-ecosystem in India - A. Kumaresan; K. M. Bujarbaruah; K. A. Pathak; Bijoy Chhetri; S. K. Ahmed; Santosh Haunshi (Tropical Animal Health and Production, 2008)

Molecular cloning, expression, and cytokinin (6-benzylaminopurine) antagonist activity of peanut (Arachis hypogaea) lectin SL-I - Monika Pathak; Bharat Singh; Amit Sharma; Praveen Agrawal; Santosh B. Pasha; Hasi R. Das; Rakha H. Das (Plant Molecular Biology, 2006)